DIY furniture : a step-by-step guide - Stuart, Christopher, ....- (London : King, 2014)
Featuring 30 new designs by leading designer-makers from around the world, DIY Furniture 2 builds on the international success of the previous title, showing you how to use simple techniques to make unique designer furniture. Including both conceptual pieces and contemporary designs in readily available materials, the book showcases an international selection of projects. Each project features hand-drawn diagrams with short, easy-to-follow instructions on how to build the piece. All the projects can be easily assembled using parts that you can find at the local DIY store, allowing the reader to create unique pieces at a fraction of the normal cost.
Keywords: Design; Meubelen